Testing of the Monitoring and Evaluation System for Subsidized Fertilizer using the Black Box Method - Rizki, Agung Mustika; Puspaningrum, Eva Yulia; Indrawanti, Annisaa Sri; Adityawan, Firza Prima (Future Science, 2023)
Evaluation and monitoring of subsidized fertilizer is needed by the Food and Agriculture Security Service to control the distribution of subsidized fertilizer. To make it easier to monitor fertilizer distribution, an information system was created that can control and monitor fertilizer supplies and distribution. At the system needs analysis stage there are several procedures related to users in the system including farmers, distributors, extension workers, and the department itself. The evaluation and monitoring system was built using the waterfall method with needs analysis, design, implementation, testing, and maintenance. At the trial stage, system testing will be carried out using the black box testing method. Testing using black box testing aims to find out errors that occur when the system is used by the end user. From the results of testing using the black box method, it was found that the functionality of the system was running well.